Clinical Evaluation Of Ketamine-Propofol Anaesthesia In Dog - Bayan, H.; Konwar , B. (Indian Journal of Veterinary Sciences and Biotechnology, 2014)
Propofol and ketamine are widely used in dogs however, both the drugs have certain limitations particularly when used singly. The effect of ketofol (ketamine+propofol) was studied in ten healthy dogs. All the animals were given ketofol I/V till effect for induction of anaesthesia and allowed to breathe room air. The quality of sedation and analgesia were satisfactory in all the animals. The heart rate, respiratory rate, rectal temperature and blood pressure were remained within the normal physiological limit. It was concluded that ketofol is safe for induction without any serious adverse affect on the normal physiological function.